Music and aspects of language acquisition - Xayrulloyeva, Lola (The Lingua Spectrum, 2025)
There are significant links between language and music, according to cognitive science research: Similar to language, music consists of perceptually distinct components arranged in hierarchically ordered sequences, making it a universal human experience. Thus, in the study of the brain processes underlying complex sound processing, language and music can act as foils for one another. Comparative research can offer fresh perspectives on the neurological and functional architecture of both domains. However, the literature discussing how that happens points out an intriguing contrast. Thus, the article shows the role of music in acquisition of language.